THE NEED TO PRIORITY THE FUNCTIONAL APPROACH IN THE DEVELOPMENT OF CREATIVE ACTIVITY IN FUTURE EDUCATORS - Raykhan Urazbaevna, Nurjanova (PT. Antis International Publisher, 2025)
Objective: To explore the integration of a functional methodology in teacher education aimed at enhancing creative skills and pedagogical competence. Method: Employing qualitative analysis and pedagogical review, the investigation considered socio-cultural influences and historical developments in preschool pedagogy, drawing on theoretical frameworks and practical case studies. Results: Findings indicate that adopting a functional approach significantly enhances the development of creative attributes in future teachers, effectively aligning pedagogical practices with evolving educational demands and social contexts. Furthermore, the dynamic evolution of pedagogical knowledge contributes to the establishment of robust methodological support, bridging the gap between theory and practice in teacher training. Novelty: The study introduces an innovative perspective on integrating functional principles within teacher education programs, offering a comprehensive framework that informs future research and practical application in enhancing creative pedagogical strategies.